Determination of chemical composition of Mucilage content extracted from Okra by FT-IR technique (Damascus University Journal of agriculture sciences, 2023)
The aim of the research was to extract (Mucilage) from the fruits of the okra plant, and to study the chemical composition of the material that was previously extracted in the laboratories of the Department of Food Sciences at the Faculty of Agricultural Engineering at the University of Damascus (Syria), where the mucilage was obtained using organic solvents and then dried and preserved as a powder. Dry for later useThe FT_IR technique was applied to identify the chemical composition and the functional groups forming the operculum extracted from the fruits of the okra plant. The resulting FT_IR spectrum contained several peaks indicating the presence of multiple functional groups that are included in the composition of mucilage.The FT_IR technique was able to determine the chemical composition of the substance within a period not exceeding 25 hours, and it can be used as a reliable method to study the chemical composition of okra mucilage. Fourier transform infrared (FT-IR) analysis
Keywords: okra; mucilage; Fourier transform infrared technology